Behavioral, normative, and control beliefs impact on the intention to offer food safety training to employees - Roberts, Kevin R.; Barrett, Betsy (My University, 2009)
Training is an important aspect of food safety programs in commercial restaurants and is integral in assuring that safe food is served. The purposes of this research were to explore the beliefs, attitudes, subjective norms, and perceptions of control of restaurant managers about providing employees the opportunity to attend food safety training, and to determine how these differ between independent and chain restaurant managers and managers with and without food safety certification. A telephone survey yielded a total of 237 responses. Results determined that intention to offer food safety training was high. Restaurant managers had a positive attitude about food safety, placed importance on the beliefs of subjective norms, and felt in control about offering food safety training. Certified managers had more positive attitudes about offering food safety training and placed greater emphasis on subjective norms, but perceived less control. Certified managers had a higher intention to train employees than non-certified managers. When comparing behavioral, normative, and control beliefs between chain and independent restaurant managers, only behavioral and normative beliefs differed. Sanitarians can use the results of this study in training and inspections to help managers overcome potential barriers to allowing employees to attend training.
Keywords: Food safety; Employees; Behavior; Subjective norms; Perceptions of control; Attitudes